Malignant Solitary Fibrous Tumour of the Breast Mimicking a Benign Tumor - Israel Barco; Clarisa González; Elena Vallejo; Antoni Pessarrodona; Nuria Giménez; Antonio García-Fernández (SAGE Publishing, 2019)
Solitary fibrous tumour (SFT) of the breast is exceedingly uncommon. Radiological assessment usually shows benign features. We report on a case of malignant SFT of the breast, while emphasizing the need for additional immunostains to reach a definitive diagnosis. Standard treatment consists of lesion removal with adequate margins.